Hybrid-fuel bacterial flagellar motors in Escherichia coli - Sowa, Y; Homma, M; Ishijima, A; Berry, R; Sowa, Y; Homma, M; Ishijima, A; Berry, R (National Academy of Sciences, 2014)
The bacterial flagellar motor rotates driven by an electrochemical ion gradient across the cytoplasmic membrane, either H(+) or Na(+) ions. The motor consists of a rotor ∼50 nm in diameter surrounded by multiple torque-generating ion-conducting stator units. Stator units exchange spontaneously between the motor and a pool in the cytoplasmic membrane on a timescale of minutes, and their stability in the motor is dependent upon the ion gradient. We report a genetically engineered hybrid-fuel flagellar motor in Escherichia coli that contains both H(+)- and Na(+)-driven stator components and runs on both types of ion gradient. We controlled the number of each type of stator unit in the motor by protein expression levels and Na(+) concentration ([Na(+)]), using speed changes of single motors driving 1-μm polystyrene beads to determine stator unit numbers. De-energized motors changed from locked to freely rotating on a timescale similar to that of spontaneous stator unit exchange. Hybrid motor speed is simply the sum of speeds attributable to individual stator units of each type. With Na(+) and H(+) stator components expressed at high and medium levels, respectively, Na(+) stator units dominate at high [Na(+)] and are replaced by H(+) units when Na(+) is removed. Thus, competition between stator units for spaces in a motor and sensitivity of each type to its own ion gradient combine to allow hybrid motors to adapt to the prevailing ion gradient. We speculate that a similar process may occur in species that naturally express both H(+) and Na(+) stator components sharing a common rotor.